Integrasi Filosofi Esensialisme dalam Kurikulum Merdeka - Khairul Tri Anjani; Anna Rufaidah; Henny Suharyati (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
This research aims to analyze the implementation of the Independent Curriculum based on the philosophical perspective of essentialism. This research uses content analysis methodology and literature study to explore the essentialist philosophical perspective of the Merdeka Curriculum. The results of this research support the essentialist view that the Independent Curriculum should give priority to principles that have been tested, are timeless and relevant. The philosophical perspective of essentialism emphasizes the value of returning to the roots of educational traditions that have proven effective in preparing students for life. The Merdeka Belajar curriculum tries to return focus to subjects that are considered basic and essential, along with efforts to improve the overall quality of education so that Indonesia can compete at the global level. Schools are seen as bearers of cultural and historical heritage, while teachers act as models who supervise students in the learning process. Conclusion, The implementation of the Independent Learning Curriculum reflects the principles of essentialism in an effort to build a solid and relevant educational foundation for the development of society and the nation, by making education an important foundation in creating virtue and success in life. Keywords: curriculum, education, essentialisme integration, independence, philosophy, philosophy